Transfacet Minimally Invasive Transforaminal Lumbar Interbody Fusion With an Expandable Interbody Device—Part II: Consecutive Case Series. Issue 5 (20th May 2020) - Khalifeh, Jawad M; Dibble, Christopher F; Stecher, Priscilla; Dorward, Ian; Hawasli, Ammar H; Ray, Wilson Z
Abstract: BACKGROUND: Advances in operative techniques and instrumentation technology have evolved to maximize patient outcomes following minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF). The transfacet MIS-TLIF is a modified approach to the standard MIS-TLIF that leverages a bony working corridor to access the disc space for discectomy and interbody device placement. OBJECTIVE: To evaluate clinical and radiographic results following transfacet MIS-TLIF using an expandable interbody device. METHODS: We performed a retrospective review of consecutive patients who underwent transfacet MIS-TLIF for degenerative lumbar spondylolisthesis. Patient-reported outcome measures for pain and disability were assessed. Sagittal lumbar segmental parameters and regional lumbopelvic parameters were assessed on upright lateral radiographs obtained preoperatively and during follow-up. RESULTS: A total of 68 patients (61.8% male) underwent transfacet MIS-TLIF at 74 levels. The mean age was 63.4 yr and the mean follow-up 15.2 mo. Patients experienced significant short- and long-term postoperative improvements on the numeric rating scale for low back pain (–2.3/10) and Oswestry Disability Index (−12.0/50). Transfacet MIS-TLIF was associated with an immediate and sustained reduction of spondylolisthesis, and an increase in index-level disc height (+0.71 cm), foraminal height (+0.28 cm), and segmental lordosis (+6.83°). Patients with preoperative hypolordosis (<40°) experienced significant increases in segmental (+9.10°) and overall lumbar lordosis (+8.65°). Pelvic parameters were not significantly changed, regardless of preoperative alignment. Device subsidence was observed in 6/74 (8.1%) levels, and fusion in 50/53 (94.3%) levels after 12 mo. CONCLUSION: Transfacet MIS-TLIF was associated with clinical improvements and restoration of radiographic sagittal segmental parameters. Regional alignment correction was observed among patients with hypolordosis at baseline. Graphical Abstract: